Analyses of the gene structure and function of olive flounder (Paralichthys olivaceus) interleukin 12 (IL-12). Issue 92 (September 2019) - Kim, Daniel; Lee, Soon Ho; Lee, Hayoung; Kim, Seong-jung; Lee, Kwan Hee; Song, Seong Kyu
Abstract: IL-12 is an important cytokine that connects the innate and adaptive immune systems. The complete gene structure of olive flounder IL-12 and its characteristics have not yet been formally reported. Here, we report the complete sequences of both subunits of olive flounder IL-12 ( IL-12p35 and IL-12p40 ). In addition, its function was analyzed by generating the single-chain rIL-12 of which subunits were fused by a GS linker and the rIL-12-specific mouse antibody. The cDNA sequences of IL-12p35 and IL-12p40 were 1059 nucleotides and 1319 nucleotides, respectively. The analyses of their gene structures, deduced amino acid sequences, protein model structures, and phylogenetic trees confirmed the accurate identification of olive flounder IL-12. The protein structure model suggested that an inter-subunit disulfide bond might be formed between the Cys177 of p35 and Cys74 of p40 to link the subunits. Olive flounder expressed IL-12p40 at higher levels than IL-12p35 in the various tissues under natural conditions although both expression levels were low. However, when infected by Edwardsiella tarda or stimulated by LPS, the flounder expressed both of the subunit genes at similar maximized levels in 6 h and gradually reduced thereafter. Olive flounder PBMC induced with the rIL-12 increased IFN-γ and TNF-α expression but decreased IL-10 expression as did treatment with LPS. However, when the LPS-treated PBMC were neutralized with the rIL-12-specific antibody, the pattern of cytokine expression was precisely reversed. In conclusion, we have formally identified the gene structure and function of olive flounder IL-12. Highlights: Olive flounder IL-12 gene consists of two subunits of IL-12p35 (1059 bp) and IL-12p40 (1319 bp). Protein modeling of olive flounder IL-12 indicates that the subunits are connected by a disulfide bond. Olive flounder IL-12 subunit genes were expressed in various tissues under natural and stimulated conditions. Olive flounder PBMC stimulated with the single chain rIL-12 increased IFN-γ and TNF-α expression but decreased IL-10 expression. When the LPS-treated PBMCs were neutralized with the rIL-12-specific antibody, the pattern of cytokine expression was precisely reversed.